MODEL KOLABORASI DALAM PELAKSANAAN PROGRAM CSR PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (PKBL) - Dika Hanjaya Anwar; Sasmito Jati Utama; M. Husni Tamrin (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2020)
This research is a collaborative model in the implementation of the community development program of green village in Jagir Wonokromo. The purpose of this study is to describe the Collaborative Model in the implementation of PKBL CSR program between PT Pertamina (Persero) MOR V Surabaya and Jagir Wonokromo Green Village in Surabaya. It applies Agranoff and Mc Guire's theories which propose six collaboration models, namely a) Jurisdiction-Based Model b) Abstinence Model c) Top-Down Model d) Donor-Recipient Model e) Reactive Model f) Contented Model. The study uses descriptive qualitative method and the aim is to find out the collaboration model in the implementation of cooperation between PT Pertamina (Persero) and green village in Jagir Wonokromo for the distribution of environmental assistance. Data collection is obtained through observation, interview, and documentation. The results indicate that the collaboration model in the Green Village environmental assistance distribution is included in the Top-Down Model.